Exploring information technology utilization and needs in community pharmacies: a cross-sectional survey in Shanghai, China - Li, Qin; Jin, Zhao; Liao, Yun; Dai, Huihua; Meng, Jie; Li, Ling (Frontiers in Pharmacology, 2025)
BackgroundCommunity pharmacists are critical in managing medication therapy and ensuring patient safety. However, in many countries, including China, challenges such as limited access to real-time patient data, fragmented communication systems, and underdeveloped clinical decision-support tools hinder the effectiveness of pharmacy services. Integrating information technology (IT) into community pharmacies can improve medication management by providing timely access to patient information, enhancing medication safety, and facilitating communication with healthcare providers.ObjectiveThis study aimed to explore the medication management practices of community pharmacists, the existing IT support available, and their specific requirements for IT-assisted medication management in community pharmacies in Shanghai, China.MethodsAn online self-assessment survey was conducted to evaluate the utilization and needs of IT-based medication management among community pharmacists in Shanghai. Demographic data and information on pharmaceutical care practices were collected and analyzed to examine correlations between these factors and the need for IT support.Results963 out of 2,178 surveys were completed over 6 months. Nearly all respondents (99.3%) provided at least one type of pharmaceutical care, but only 0.93% offered all types. Regarding current utilization and needs for IT systems, community pharmacists rated access to patient/medication information and digital standardized documentation flow as poor satisfaction with the highest level of needs. Multivariate regression analysis showed that IT needs were significantly associated with time spent in clinical pharmacy practice, time dedicated exclusively to clinical pharmacy, and the number of prescriptions dispensed weekly.ConclusionWhile community pharmacists are key in providing pharmaceutical care, IT support remains inadequate. There is a pressing need for an integrated IT system that offers real-time access to patient medical information, a standardized documentation system, improved clinical decision support software, and enhanced communication with other healthcare providers.